Estudio de la situación socio-lingüística del kichwa en la comunidad Pucará de Cangahu - Acero Acero, Wilmer Efraín (2015)
The study of the socio-linguistic situation in Pucara Kichwa community Cangahua aims to give an assessment of the reality of Kichwa in this community. In carrying out this work important fragments of the history of the community, different lifestyles, and the influence of education on the attitudes of the speakers against the indigenous language was also collected. To sociolinguistic research on the vitality of the Kichwa works of some authors in order to meet theoretical and practical elements and methodologies used in their studies was revised. Some authors worked more on describing the situation of the language, while others focused more on finding strategies to revitalize their languages. In Ecuador there are two sociolinguistic research conducted in the last decade of the twentieth century. The first was coordinated by Thomas Büttner, and the other was organized by Marleen Haboud based on previous data. The sociolinguistic reality of the Kichwa community in Pucara Cangahua. Instruments was designed to gather information from parents, children and community leaders. I was tabulated with these results, in girls and boys understand something without having. The elderly comprise all but some no longer speak. However in the investigation it was found that girls and children from the school that is in the community, have a positive attitude relearn the Kichwa language